Strain-Dependent Inhibition of Erythrocyte Invasion by Monoclonal Antibodies Against Plasmodium falciparum CyRPA - Knudsen, Anne S.; Björnsson, Kasper H.; Bassi, Maria R.; Walker, Melanie R.; Kok, Andreas; Cristinoi, Bogdan; Jensen, Anja R.; Barfod, Lea (Frontiers in Immunology, 2021)
The highly conserved Plasmodium falciparum cysteine-rich protective antigen (PfCyRPA) is a key target for next-generation vaccines against blood-stage malaria. PfCyRPA constitute the core of a ternary complex, including the reticulocyte binding-like homologous protein 5 (PfRh5) and the Rh5-interacting protein (PfRipr), and is fundamental for merozoite invasion of erythrocytes. In this study, we show that monoclonal antibodies (mAbs) specific to PfCyRPA neutralize the in vitro growth of Ghanaian field isolates as well as numerous laboratory-adapted parasite lines. We identified subsets of mAbs with neutralizing activity that bind to distinct sites on PfCyRPA and that in combination potentiate the neutralizing effect. As antibody responses against multiple merozoite invasion proteins are thought to improve the efficacy of blood-stage vaccines, we also demonstrated that combinations of PfCyRPA- and PfRh5 specific mAbs act synergistically to neutralize parasite growth. Yet, we identified prominent strain-dependent neutralization potencies, which our results suggest is independent of PfCyRPA expression level and polymorphism, demonstrating the importance of addressing functional converseness when evaluating blood-stage vaccine candidates. Finally, our results suggest that blood-stage vaccine efficacy can be improved by directing the antibody response towards defined protective epitopes on multiple parasite antigens.